Aspects of the symplectic and metric geometry of classical and quantum physics - Russell, Neil Eric (Rhodes University, Faculty of Science, Department of Physics and Electronics, 1993)
I investigate some algebras and calculi naturally associated with the symplectic and metric Clifford algebras. In particular, I reformulate the well known Lepage decomposition for the symplectic exterior algebra in geometrical form and present some new results relating to the simple subspaces of the decomposition. I then present an analogous decomposition for the symmetric exterior algebra with a metric. Finally, I extend this symmetric exterior algebra into a new calculus for the symmetric differential forms on a pseudo-Riemannian manifold. The importance of this calculus lies in its potential for the description of bosonic systems in Quantum Theory.
Keywords: Symplectic manifolds; Geometry, Differential; Geometric quantization; Quantum theory; Clifford algebras